2016
DOI: 10.1371/journal.pone.0168352
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Role of Metabolic Determinants on the Relationship between Insulin Sensitivity and Secretion

Abstract: BackgroundInsulin secretion correlates inversely with insulin sensitivity, which may suggest the existence of a crosstalk between peripheral organs and pancreas. Such interaction might be mediated through glucose oxidation that may drive the release of circulating factors with action on insulin secretion.AimTo evaluate the association between whole-body carbohydrate oxidation and circulating factors with insulin secretion to consecutive oral glucose loading in non-diabetic individuals.MethodsCarbohydrate oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The second point, and likely more relevant, refers to the fact that insulin variance is just another way to describe hyperinsulinemia. From our studies, serum insulin variance calculated over 3 h (eight time points) after an OGTT was highly related with average insulinemia ( r = 0.84; p < 0.0001; n = 51; unpublished analysis from Galgani, Gomez et al 24 ). The concept elaborated in this review considers crucial the inclusion of fuel availability at tissue/cellular level to identify cellular/molecular determinants of MetF.…”
Section: Analytical Issues In the Determination Of Metfmentioning
confidence: 58%
See 2 more Smart Citations
“…The second point, and likely more relevant, refers to the fact that insulin variance is just another way to describe hyperinsulinemia. From our studies, serum insulin variance calculated over 3 h (eight time points) after an OGTT was highly related with average insulinemia ( r = 0.84; p < 0.0001; n = 51; unpublished analysis from Galgani, Gomez et al 24 ). The concept elaborated in this review considers crucial the inclusion of fuel availability at tissue/cellular level to identify cellular/molecular determinants of MetF.…”
Section: Analytical Issues In the Determination Of Metfmentioning
confidence: 58%
“…During fasting, endogenous fatty acid supply is abundant, 23 which increases its contribution to ATP production, thus progressively replacing the glucose supply. Upon ingestion of foods containing carbohydrates, glucose supply increases and thus boosts glucose oxidation as the main energy source 24 . This ability to alternate energy fuels depending on fuel availability (i.e., MetF) assures a constant and sufficient energy supply to organs and cells.…”
Section: Definition Of Metfmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas exchange was measured over the last 20 minutes of each hour after each OGTT, which was followed by the indirect calorimetry correction procedure. Blood analysis as well as corrected metabolic rate and RQ were reported elsewhere .…”
Section: Methodsmentioning
confidence: 99%
“…Some of them (IL6, fractalkine/CX3CL1, and RANTES/CCL5) have been also shown to influence in vitro insulin secretion [ 4 , 5 , 19 , 20 ]. In turn, we recently reported that circulating IL8/CXCL8 concentration directly associates with in vivo insulin secretion in humans [ 21 ].…”
Section: Introductionmentioning
confidence: 99%